Analysis of The Effectiveness of Spelling Puzzle Media for Mastering The Vocabulary of Autism Children - Herliyanti, Arinda; Junaidi, Ahsan Romadlon; Novianti, Ranti (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Autistic students experience barriers in communication. These barriers make it difficult for students to understand two-way communication due to their lack of vocabulary. Increasing the number of vocabulary is delivered using spelling puzzle media. The aim of this research is to analyze the effectiveness of spelling puzzle media to increase understanding of the vocabulary of autistic children. The method used in this research is pre-experimental with a one group pretest-posttest design. The subjects of this research were 6 Autistic class I students at SLB 1 Gondang Tulungagung. The students' pretest and posttest results were analyzed based on the gain score criteria, showing a score of 0.7 which was in the medium criteria. These criteria show an increase in the number of students' vocabulary after learning using spelling puzzle media.